Explanation:
length = the original length
width = the original width
length = width + 10 or
width = length - 10
(length + 4) × (width + 8) = 135
A
now we are using the first equation in the second to solve then for length :
(length + 4) × (length - 10 + 8) = 135
(length + 4) × (length - 2) = 135
length² - 2×length + 4×length - 8 = 135
length² + 2×length = 143 or
length² + 2×length - 143 = 0
this is the equation to model the scenario.
solving in general such a quadratic equation :
x = (-b ± sqrt(b² - 4ac))/(2a)
in our case
x = length
a = 1
b = 2
c = -143
length = (-2 ± sqrt(2² - 4×1×-143))/(2×1) =
= (-2 ± sqrt(4 + 572))/2 =
= (-2 ± sqrt(576))/2 =
= (-2 ± 24)/2 = (-1 ± 12)
length1 = -1 + 12 = 11
length2 = -1 - 12 = -13
a negative solution for a length is not applicable, so,
length = 11
width = length - 10 = 11 - 10 = 1
B
the expanded length = 11 + 4 = 15
the expanded width = 1 + 8 = 9
the expanded perimeter is then
2×15 + 2×9 = 30 + 18 = 48